2019
DOI: 10.3400/avd.cr.19-00084
|View full text |Cite
|
Sign up to set email alerts
|

Successful Balloon-Occluded Retrograde Transvenous Obliteration for Gastric Varices Using Foam Sclerosant Followed by Glue Embolization of Gastrorenal Shunt via the Brachial Vein Approach in a Severely Obese Patient

Abstract: Balloon-occluded retrograde transvenous obliteration is an effective treatment for gastric varices. In this report, we illustrate a consecutive treatment strategy via brachial vein approach and n-butyl cyanoacrylate (NBCA) packing of the gastrorenal shunt (GRS) after injecting sclerosing agent in a severely obese patient. The brachial vein approach reduced the burden on the patient, and the closure of the GRS using NBCA shortened the procedure time. These techniques may improve patient comfort as well as reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Small collateral veins are generally embolized prior to sclerosing agent injection to prevent leakage of the sclerosing agent or varix recurrence [ 81 , 82 , 83 , 84 ]. Tsuruya et al reported a case where NBCA-Lipiodol ® were used for gastrorenal shunt embolization after injecting sclerosing agent in a severely obese patient, resulting in a shorter procedure time [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small collateral veins are generally embolized prior to sclerosing agent injection to prevent leakage of the sclerosing agent or varix recurrence [ 81 , 82 , 83 , 84 ]. Tsuruya et al reported a case where NBCA-Lipiodol ® were used for gastrorenal shunt embolization after injecting sclerosing agent in a severely obese patient, resulting in a shorter procedure time [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…To lower the cost and shorten the procedure time, we injected n -butyl cyanoacrylate (nBCA) to embolize the GRS after sclerosant injection (case 1). Before now, the use of nBCA in BRTO was previously reported in a case report, in which it was injected after injecting a foam sclerosant into a GV via a brachial vein approach [7] . In this report, we describe three consecutive patients in whom GVs were treated by nBCA-assisted retrograde transvenous obliteration (NARTO), after a case (case 1) in whom nBCA was injected after coil placement.…”
Section: Introductionmentioning
confidence: 99%